Double Laplace Transform Method for Solving Space and Time Fractional Telegraph Equations - Ranjit R. Dhunde; G. L. Waghmare (International Journal of Mathematics and Mathematical Sciences)
Double Laplace transform method is applied to find exact solutions of linear/nonlinear space-time fractional telegraph equations in terms of Mittag-Leffler functions subject to initial and boundary conditions. Furthermore, we give illustrative examples to demonstrate the efficiency of the method.